Use of social media, student engagement, and academic performance of business students at Universiti Utara Malaysia - Alshuaibi, Mohamad Sa'id Ibrahim (2015)
Social media is considered an important phenomenon in today’s generation and is more popular among youngsters in many nations. This study aims to investigate the effect of social media on academic performance of students of College of Business at Universiti Utara Malaysia through the mediation of student engagement using self-determination theory. A total number of 227 students were randomly chosen to participate in this study. Questionnaire was used as the main data collection technique, which was personally administered during class sessions. Structural equation modelling-partial least square (SEM-PLS) was used as the main data analysis to test the research hypotheses. Result showed no direct relationship between social media and academic performance, but the effect was mediated by agentic engagement and behavioural engagement. The result suggests that social media has the potential to be used in a learning environment as it promotes engagement of student in class and subsequently their academic performance and success. Recommendations for future research and limitations of the study are also highlighted